Myositis ossificans circumscripta of the triceps muscle in a Rottweiler dog - Tambella, A. M.; Palumbo Piccionello, A.; Dini, F.; Vullo, C.; Rossi, G.; Scrollavezza, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A 20-month-old male Rottweiler dog was presented with the complaint of chronic right forelimb lameness that was unresponsive to conservative treatment. Physical examination allowed for the topographical identification of the source of the problem as a firm enlargement of the soft tissues that was partially movable from humeral bone and compatible with an alteration of the triceps brachii muscle. Radiographic images showed signs that were highly suggestive of myositis ossificans. Computed tomography allowed for a more accurate characterization of the lesion, to exclude involvement of the elbow joint and humeral bone, and to localize anatomically the lesion in the caput accessorium and longum of the triceps brachii muscle. Surgical excision of the ossified portion of the triceps muscle was performed. Histological examination of the excised tissue substantiated the diagnosis of myositis ossificans. A one year clinical and radiographic follow-up examination showed a complete recovery, with no evidence of complications or recurrence. Despite myositis ossificans in dogs having previously been identified in the hindlimbs, this case of myositis ossificans circumscripta of the triceps muscle suggests that it may also occur in the muscles of the forelimb.
Keywords: Myositis ossificans; triceps muscle; lameness; dog